Wokół idei ekologii akustycznej. Koncepcje i praktyki - Losiak, Robert (Studia Etnologiczne i Antropologiczne, 2017)
The idea of acoustic ecology emerged in the sixties of the twentieth century with the work of Raymond Murray Schafer and his school of soundscape studies. The starting point was the concern for the sound environment resulting from the sense of threat from progressive civilization changes and the increase of noise. In his project work, Schafer gave emphasis to education as well as to the development of ecological acoustic design. What was another important element of the program was the research activity aimed at, among others, documenting and analysing contemporary landscapes. The ecological importance of this research arises from increasing social awareness about the cultural value of the sound environment.